Contextual Teaching and Learning (CTL) as a Strategic Driver for Student Engagement in Fiqh Education - Fatqur Rohim; Sunarto Sunarto; Dedi Setiawan (Assyfa Journal of Islamic Studies, 2026)
This research is motivated by the low level of student learning motivation in Fiqh subjects, characterized by minimal active participation and suboptimal learning outcomes. This study aims to analyze the strategies of Fiqh teachers in implementing the Contextual Teaching and Learning (CTL) model, identify supporting and inhibiting factors, and analyze its impact on student learning motivation at MTsN 1 Mesuji. This study employs a qualitative approach with a field research design, selecting informants through purposive sampling, including Fiqh teachers, the vice-principal for curriculum, and students. Data collection techniques included structured interviews, participant observation, and documentation, and the data were analyzed using the Miles and Huberman interactive model. The results show that Fiqh teachers' strategies for implementing CTL are carried out systematically through planning, implementation, and evaluation, integrating the principles of constructivism, inquiry, learning community, modeling, and authentic assessment. The implementation of CTL proved effective in enhancing student learning motivation, evidenced by increased activeness in discussions, willingness to ask questions, and enthusiasm in learning practices, alongside a significant increase in average test scores exceeding the minimum mastery criteria. The main supporting factors include madrasah policies and student enthusiasm, while inhibiting factors include time constraints and large class sizes. In conclusion, the CTL model serves as an effective strategic driver for increasing student engagement and learning motivation in Fiqh education.